Species-Specificity of Transcriptional Regulation and the Response to Lipopolysaccharide in Mammalian Macrophages - Bush, Stephen J.; McCulloch, Mary E. B.; Lisowski, Zofia M.; Muriuki, Charity; Clark, Emily L.; Young, Rachel; Pridans, Clare; Prendergast, James G. D.; Summers, Kim M.; Hume, David A. (Frontiers in Cell and Developmental Biology, 2020)
Mammalian macrophages differ in their basal gene expression profiles and response to the toll-like receptor 4 (TLR4) agonist, lipopolysaccharide (LPS). In human macrophages, LPS elicits a temporal cascade of transient gene expression including feed forward activators and feedback regulators that limit the response. Here we present a transcriptional network analysis of the response of sheep bone marrow-derived macrophages (BMDM) to LPS based upon RNA-seq at 0, 2, 4, 7 and 24 hours post-stimulation. The analysis reveals a conserved transcription factor network with humans, and rapid induction of feedback regulators that constrain the response at every level. The gene expression profiles of sheep BMDM at 0 and 7 hours post LPS addition were compared to similar data obtained from goat, cow, water buffalo, horse, pig, mouse and rat BMDM. This comparison was based upon identification of 8200 genes annotated in all species and detected at >10TPM in at least one sample. Analysis of expression of transcription factors revealed a conserved transcriptional millieu associated with macrophage differentiation and LPS response. The largest co-expression clusters, including genes encoding cell surface receptors, endosome-lysosome components and secretory activity, were also expressed in all species and the combined dataset defines a macrophage functional transcriptome. All of the large animals differed from rodents in lacking inducible expression of genes involved in arginine metabolism and nitric oxide production. Instead, they expressed inducible transporters and enzymes of tryptophan and kynurenine metabolism. BMDM from all species expressed high levels of transcripts encoding transporters and enzymes involved in glutamine metabolism suggesting that glutamine is a major metabolic fuel. We identify and discuss transcripts that were uniquely expressed or regulated in rodents compared to large animals including ACOD1, CXC and CC chemokines, CD163, CLEC4E, CPM, CSF1, CSF2, CTSK, MARCO, MMP9, SLC2A3, SLC7A7 and SUCNR1. Conversely, the data confirm the conserved regulation of multiple transcripts for which there is limited functional data from mouse models and knockouts. The data provide a resource for functional annotation and interpretation of loci involved in susceptibility to infectious and inflammatory disease in humans and large animal species.